The Sitnikov problem for several primary bodies configurations - Beltritti, Gastón (2018)
In this paper we address an n+ 1 -body gravitational problem governed by the Newton’s laws, where n primary bodies orbit on a plane Π and an additional massless particle moves on the perpendicular line to Π passing through the center of mass of the primary bodies. We find a condition for the described configuration to be possible. In the case when the primaries are in a rigid motion, we classify all the motions of the massless particle. We study the situation when the massless particle has a periodic motion with the same minimal period as the primary bodies. We show that this fact is related to the existence of a certain pyramidal central configuration.